5‐Aminolevulinic acid patch (Alacare) photodynamic therapy for actinic cheilitis: data from a prospective 12‐month follow‐up study on 21 patients. (10th March 2020) - Radakovic, S.; Dangl, M.; Tanew, A.
Abstract: Background: Actinic cheilitis (AC) is a variant of actinic keratosis (AK) affecting the lips and caused by chronic ultraviolet exposure. Objective: Alacare is a self‐adhesive, skin‐coloured 5‐aminolaevulinic acid patch that has been developed for use in photodynamic therapy (PDT) of mild‐to‐moderate AK. Based on promising preliminary results in the treatment of AC with Alacare patch PDT, we decided to extend our previous investigation to gain more data on the efficacy, tolerability, safety and cosmetic outcome of Alacare patch PDT for AC. Methods: Twenty‐one patients with a clinical diagnosis of mild‐to‐moderate AC were included in the study and subjected to one single session of PDT. After occlusion with the Alacare patch for 4 h, the AC lesions were illuminated for 10 min with red light at a dose of 37 J/cm 2 . All patients received local anaesthesia prior to illumination. Additionally, all lesions were cooled during PDT with a cold air blower. PDT‐induced pain and skin phototoxicity were monitored during and up to 7 days after PDT. Clinical assessment of efficacy, cosmetic outcome and global patient satisfaction was performed at 3, 6 and 12 months after treatment. Results: Nineteen patients completed the study. Three months after PDT, 17 patients (89.5%) had achieved complete remission. Of these, one patient presented with recurrence of AC at the 6‐month follow‐up, whereas all other patients remained in remission until the end of the observation period. The complete clinical cure rate at 1 year after a single Alacare patch PDT thus was 84.2%. Pain during illumination and the phototoxic skin reaction were in general mild to moderate. The cosmetic outcome was excellent. Conclusion: The present prospective study on Alacare patch PDT for AC confirms its high clinical efficacy, good tolerability and favourable cosmetic effects. Alacare patch PDT should be considered as a valid treatment option for patients with AC.